Pengaruh Profitabilitas, Kepemilikan Institusional, Dewan Komisaris Independen, dan Dewan Direksi terhadap Sustainability Report Disclosure - Septi Ludianah; Dirvi Surya Abbas; Imam Hidayat; Triana Zuhrotun Aulia (BADAN PENERBIT STIEPARI PRESS, 2022)
The purpose of this study is to empirically prove the effect of profitability, Institutional Ownership Independent Board of Commissioners and Board of Directors Towards Sustainability Report Disclosure (In Sector Companies Mining Listed on the Indonesia Stock Exchange for the Period 2018 – 2021 ) The population of this study includes all companies in the mining sector listed on the Indonesia Stock Exchange (IDX) for the period 2018-2021. Technique sampling using purposive sampling technique. Based on predetermined criteria obtained 10 companies. Type of data used is secondary data obtained from the official website of each company mining. The analytical method used is data logical regression analysis panel. The results showed that profitability, institutional ownership and The Independent Board of Commissioners has no effect on the Sustainability Report Disclosure, while the Board of Directors has a significant positive effect Sustainability Report Disclosure. Taken together, the research shows that Profitability, Institutional Ownership, Independent Board of Commissioners and Board of Directors on Sustainability Report Disclosure.